Decision comfort and student engagement in higher education - Roy, Sanjit; Japutra, Arnold; Singh, Gaganpreet; Chakraborti, Rajdeep (Routledge, 2023)
In today’s dynamic service environment,the higher education sector has maintained steady growth. The incorporation of technology in the process of teaching engages the students in the classroom,however,the students tend to indicate lower levels of engagement. Although engagement in the classroom is pivotal for student success,a robust understanding of the means to enhance student engagement is quite scarce. Thus,this study examines a robust research framework to have a better understanding of student engagement. Derived from the survey of university students,the proposed research hypotheses were tested. Results show that co-production behaviour and decision comfort are prominent drivers of student engagement. Results also show that decision comfort mediates the path between students’ goal intention and student engagement. Finally,we discuss the managerial and theoretical implications. © 2023 Informa UK Limited,trading as Taylor & Francis Group.
Keywords: Co-production behaviour; Decision comfort; Goal intention; Student engagement; ODS 16 - Paz, justicia e instituciones sólidas